Neural correlates of error prediction in a complex motor task - Maurer, Lisa Katharina; Maurer, Heiko; Müller, Hermann (Frontiers in Behavioral Neuroscience, 2015)
The goal of the study was to quantify error prediction processes via neural correlates in the Electroencephalogram. Access to such a neural signal will allow to gain insights into functional and temporal aspects of error perception in the course of learning. We focused on the error negativity (Ne) or error‐related negativity (ERN) as a candidate index for the prediction processes. We have used a virtual goal-oriented throwing task where participants used a lever to throw a virtual ball displayed on a computer monitor with the goal of hitting a virtual target as often as possible. After one day of practice with 400 trials, participants performed another 400 trials on a second day with EEG measurement. After error trials (i.e. when the ball missed the target), we found a sharp negative deflection in the EEG peaking 250 ms after ball release (mean amplitude: t = -2.5, df = 20, p = .02) and another broader negative deflection following the first, reaching from about 300 ms after release until unambiguous visual KR (hitting or passing by the target; mean amplitude: t = -7.5, df = 20, p < .001). According to shape and timing of the two deflections, we assume that the first deflection represents a predictive Ne/ERN (prediction based on efferent commands and proprioceptive feedback) while the second deflection might have arisen from action monitoring.